Forecasting habitat suitability of tropical karst plants in a warmer world — Thailand’s Begonia diversity as a key example - Radbouchoom, Sirilak; delos Angeles, Marjorie D.; Ngarega, Boniface K.; Phutthai, Thamarat; Schneider, Harald (Frontiers in Plant Science, 2025)
Tropical karst habitats host a rich plant diversity, of which many species are edaphic specialists with narrow distribution ranges. Many of these plants are expected to be highly vulnerable to global climate change as a consequence of the substantial fragmentation of karst formations in combination with edaphic preferences and dispersal limitations. In recent years, the application of species distribution models to predict range under future climate scenarios has increasingly become a popular tool to guide conservation management approaches. Here, we examined the impact of climate change on the genus Begonia in Thailand using an ensemble modelling approach. The models incorporated climatic data and the geological characteristics of karst formations to reliably predict the distribution of species that reside within karst habitats. Our results revealed that the diversity of Begonia species in karst environments is primarily influenced by key climatic factors, including the mean temperature of the wettest quarter and annual precipitation, along with geographical features such as karst formations. Together, these elements significantly shape the distribution patterns of Begonia diversity in these unique habitats. Under current climatic conditions, clusters of suitable habitats for Begonia were found in Northern, South-Western, and Southern Thailand. The employed scenarios for future warmer climates converged to predict a substantial loss of currently suitable habitats. Applying the moderate SSP245 scenario, the model predicted range losses of 32.46% in 2050 that accumulate to 38.55% in 2070. Notably, more worrying predictions were obtained by applying the worst-case (SSP585) scenario, which projected a range loss of 37.73% in 2050 and increasing to 62.81% in 2070. In turn, the gain by areas becoming suitable was much lower than the loss. These results are highly consistent with the predicted high vulnerability of karst plants to global climatic change. Conservation efforts require taking into account these predictions by focusing on two key actions. Firstly, protecting areas where occurrences of Begonia are predicted to be less affected by climate change. The assignment of these areas to national parks thus far has not been achieved yet. Secondly, establishing practical conservation strategies for Begonia species occurring preliminary or even exclusively in karst landscapes.